Optimal configuration of acquisition terminals in regional distribution grids considering dynamic observability - Xuan, Yi; Huang, Jianping; Sun, Zhiqing; Zhang, Tianyang; Liang, Yundan; Dai, Tiechao; Liu, Weihao; Liu, Jian; Huang, Yi; Fan, Libo; Liu, Yingye (Frontiers in Energy Research, 2024)
Optimizing the configuration of acquisition terminals can maximize the observability and state estimation accuracy of the distribution grid achieving comprehensive perception of the distribution grid. However, the existing optimization configuration methods typically target a single topology structure. For regional distribution grids with dynamic topology changes, it cannot meet the observability requirements of all their topologies. In this regard, this paper proposes an optimal configuration scheme for regional distribution grid acquisition terminals considering dynamic observability. Firstly, the regional distribution grid considering the change of contact switch is modeled. Based on the observation redundancy and state estimation accuracy, the dynamic observability index of regional distribution grid is proposed. Then, a multi-objective optimal configuration model of acquisition terminal is constructed with the objective function of maximizing dynamic observability and minimizing configuration cost. Finally, the effectiveness of the proposed approach is validated with the simulation model.